NEW ST&I FRAMEWORK OF PARANÁ STATE: INTRODUCTORY ANALYSIS ON INSTRUMENTS TO STIMULATE INNOVATION IN COMPANIES (Interdisciplinary Studies Journal, 2024)
This article studies the instruments to stimulate innovation in companies arranged in the Science, Technology and Innovation Framework of Paraná (Law n. 20.541/2021), hereinafter MCTI/PR. The objective is to reflect, even if in a non-exhaustive way, what are the instruments of stimulus to innovation in companies, classifying them as tools of public policies of supply and public policies of demand. To do so, it uses geographic (federal and state legislation) and temporal (new Framework and revoked law) clippings. It is concluded that the MCTI/PR included tools that foster innovation especially aimed at startups, as well as is more concerned with technological innovations and, finally, that the instruments are compatible with the principles set out in the same Law. The real compatibility and concrete effects can only be observed from the development and evaluation of appropriate public policies. The incentives provided in the MCTI/PR tends to give greater legal security to the legal relations and business agreed upon.
Keywords: Public Policies; Companies; Innovation Incentives; Brazil; Paraná